What in your right mind would make you do that?? Proximate and ultimate mechanisms of plasticity in mating strategies by the Trinidadian guppy (Poecilia reticulata) - Dolphin, Kimberly, author; Hoke, Kim, advisor; Mueller, Rachel, committee member; Seger, Carol, committee member; Ghalambor, Cameron, committee member (Colorado State University. Libraries, 2020)
All animals must make decisions every day and often these decisions are directly linked to fitness outcomes, meaning better decisions are expected to be associated with higher fitness. Rapid decisions between alternative strategies allow animals to behave more appropriately for their environment. Thus, selection will shape not only how animals will respond to cues at different timescales, but also what cues they respond to at different timescales. Neural substrates of decisions are a vital component for our understanding of how experiences on different timescale influence decision-making strategies. The sensitivity of sensory systems to specific cues is tuned by genetics and then subsequently refined through developmental neural plasticity. The goal of this dissertation is to fill in gaps in understanding how experiences across multiple timescales influence neural mechanisms and behavioral strategies. I chose to address this question with the alternative mating strategies of male Trinidadian guppies (Poecilia reticulata), a sexually dimorphic tropical fish native to the island of Trinidad. In chapter two we compared how ancestral predation pressures influenced sensitivity to developmental exposure to predator cues and how those two timescales interacted to shape activity and reproductive behaviors when males were in different social contexts. Evolutionary history shaped how developmental contexts influence the resulting behavioral phenotypes across multiple acute contexts. However, the influence of experiences across timescales were not consistent between behaviors. We then extended our study further in chapter three to investigate how developmental experiences with conspecifics influenced males' later abilities not only to respond to virgin and recently mated females, but also to refine mating strategies in response to the female behaviors over multiple exposures. Social experiences during developmental timescales also had distinct influences on the expression of the two reproductive strategies in chapter three. We showed that males modulated and refined mating strategies relatively independently of each other in relationship to their rearing experiences. We concluded with an investigatory probe into the cellular identities of neurons that are responding to a reproductive context in chapter four using a phosphoTRAP RNA-seq protocol. Chapter four provides evidence that several neuromodulatory pathways respond to cues in a reproductive context, which could point to constraints on evolution. In sum, this dissertation used an integrative approach to understand how experiences across multiple timescales influence decisions. We bridged several fields that can help provide insight into the evolution of decision-making processes and allow us to make future hypotheses about influences of multiple experiences with complex cues.
Keywords: courtship; evolution; neuroethology; decision-making; behavior; guppy